Atomisers for the Aerial Application of Pesticides in Tsetse (Glossina sp) and Armyworm (Spodoptera exempta) Control - Kinnersley, Robert P. (Cranfield University, 1992)
Aerial application of insecticides is likely to remain an important component in realistically-costed vector and migratory pest control operations for the foreseeable future. The objective of this work was to identify or design improved atomisers for use in two such operations, tsetse (Glossina sp. ) and African armyworm (Spodoptera exempta) control, the former requiring an insecticide aerosol ýx'ith a VMD of 20 to 30ýim at rates upto 0.5 litres/minute and the latter a fine spray with a VMD of 80 to 120ýtm at rates around 16 litres/minute. In both cases rotary atomisation was confirmed as the most appropriate technique. Assessments were made of seven commerciall%, available atomisers and two existinc, prototypes, on the basis of existing reports and new data generated under simulated flight conditions in a wind tunnel. Droplet sizing was carried out using an optical array probe set to give a resolution of 54m over a range of 3.6 -3) 12.54m. None of the atomisers tested met the specification for tsetse-spraying, the limiting factors being rotation speed and inability to distribute low volumes of liquid across their full atomising surface. The Micronair AU4000 and AU5000 and the Micron X-I were found to be suitable for armyworm control, the Micron X-1 having the additional ability to produce spray with VMDs down to 40ýim. A review of rotary atomiser literature provided design guidelines for the design of an atomiser capable of meeting tsetse specifications. The principle effect of liquid flow 4D within the atomiser was found to be on the uniformity of fluid distribution. Premature ligament formation and formation of cross-flow vortices were identified as factors which could adversely influence fluid distribution under some conditions. Ligzan ment seperation from disks can be aided byI slender teeth, providing that these have a spaciniz similar to the natural spacing of ligaments predicted by Taylor instability theoInry . The effect of rotation speed and atomiser diameter on droIp let diameter is determined by the degree of stretching of the ligament due to its acceleration relative to the atomiser, implying that a finer spray would be achieved using a smaller rotating diameter disc than a larger diameter disc with the same peripheral speed. A series of experimental studies was carried out usinrgD higZDh speed photogZ_r_a phy in conjunction with the droplet sizinaprobe. Disturbancesh a,,i,n, g the forrn predicted for C cross-flow vortices were observed in liquid on a plain spinning disc. A sin(-)'Ieligament generator was constructed. With increasing rotation speed this rt\'taled a series of increasingly unstable ligament disintegration modes in which interaction with the surroundin4g15 air became a controlling-- factor. Complete shattering of the ligament occured at a Weber number of between 4 and 5, similar to reported values for liquid jets in a cross flo%v of cyas. Droplet sizing indicated that the specified performance for tsetse operations could be obtained from 50mm diameter atomisers with a total of around _'30000is suing points at a rotation speed of 26000 RPNI. This Zý sucy(yestecdN l,i ndcr rather than disc-based atomisers. A slit was found to be impractical as a means of distributing liquid unifom-ily at high rotation speeds but distribution was sucýe: ssfully achieved using a porous flow resistor. Prototype wind- and electi-ically-driven atornisers were constructed using rotating porous cylinders fed internally by spray bars designed with the help of finite element methods. Ligament formation was found to occur from a film of liquid on the outer surface of the cylinder, the variation in spacing with feedrate and rotation speed suggesting Taylor instability to be the controlling factor. The prototype atomisers achieved a performance suitable for tsetse control operations. This was not enhanced by the provision of discrete issuing points.